Development of ethnofun to improve computational thinking of junior high school students grade VII - Romandoni, Hendrisa Rizqie; Maharani, Swasti; Suprapto, Edy (Al-Jabar: Jurnal Pendidikan Matematika, 2024)
Background: There is a lack of ethnomathematics learning media for junior high school students on the subject of spatial geometry, hindering the development of their computational thinking skills.Aim: This study aims to develop learning media to enhance students' computational thinking by leveraging ethnomathematics principles.Method: The research employed the Research and Development (R&D) method using the AADIE model, focusing on designing and implementing ethnomathematics-based learning media.Result: The validation score of the developed media reached 86%, indicating a high level of validity, while the student response questionnaire yielded an 88.89% validation score. The practicality assessment of the ethnofun learning media also scored 86.25%.Conclusion: The results of the study indicate that ethnomathematics-based learning media have valid and practical criteria for use in improving computational thinking skills of junior high school students. High validity and practicality values indicate that the developed ethnofun media is a feasible tool to improve understanding of spatial geometry and foster students' computational thinking skills.